The Role of Organizational Culture in the Influence of HR Practices, Knowledge Management, and Talent Management on Organizational Performance - Setyawan, Agustinus (JDM (Jurnal Dinamika Manajemen), 2021)
The objective of this research is to analyze the effect of human resource management practices, knowl- edge management, and talent management on organizational performance by mediating organization- al culture in the mining industry. The design used in this research is hypothesis testing using structural equation modeling. The population of respondents in this study were employees at the management level of mining companies in East Kalimantan Province. The sample collection of respondents is car- ried out proportionally to company employees based on production capacity per year with purposive sampling method, where the number of samples that meet the criteria for analysis is from 127 employ- ees of coal mining companies taken from 10 existing companies. From the research results, there are three direct relationship hypotheses that are accepted and four hypotheses are rejected. Organizational culture as a full mediation of the relationship between HRM practice and talent management on or- ganizational performance, while only as a partial mediation on the relationship between knowledge management and organizational performance. Future research can focus on social and environmental issues in the mining industry in Indonesia or other countries.